Development of an adaptive bypass element for passive entrainment flow control in dry powder inhalers. (August 2019) - Kopsch, Thomas; Murnane, Darragh; Symons, Digby
The release of drug from dry powder inhalers is strongly dependent on the patient's inhalation profile. To maximise the effect of the treatment, it is necessary to optimise dry powder inhalers to achieve drug delivery that (A) is independent of the inhalation manoeuvre and (B) is targeted to the correct site in the lung. The purpose of this study is to develop a dry powder inhaler with an adaptive bypass element that achieves desired drug delivery behaviour. Computational and experimental methods are used. First, the effect of a generic variable bypass element on entrainment behaviour is modelled. This is done by modelling a dry powder inhaler as a network of flow. Second, the behaviour of a potential variable bypass element, a flap valve, is studied both computationally and experimentally. Third, the flow resistances are optimised to achieve consistent and desired entrainment behaviour for patients with very different inhalation manoeuvres. A simulated dry powder inhaler device design was found that achieves an approximately constant entrainment flow rate of 12 L/min when total flow rates larger than 20 L/min are applied. The developed dry powder inhaler is predicted to accurately deliver drug for patients with highly different inhalation manoeuvres.